Bortom gränserna. Ett brevsamtal om språk, tillhörighet och dekolonisering - Knobblock, Ina; Stubberud, Elisabeth (Tidskrift för genusvetenskap, 2021)
This article is a co-authored conversation in letters about lived experiences of Sámi and Kven/Tornedalian belonging, decolonisation, and feminism. The text contributes to a growing research field that combines Indigenous studies and gender research in the Nordic countries. In this article we focus on embodied and affective minority-experiences within colonial and decolonial processes, and also explore forms of knowledge production based on Indigenous relational epistemes. We do this by using a creative and open-ended writing style, learning with one another through dialogue and interchange, and exploring our connections to land and communities to heal and re-create relations. In the letters, we move across interconnected analytical themes. We discuss language, including affectivity and vulnerability in language revitalisation. We also write about place and belonging and the in-between spaces of academia and our social and geographical spaces of origin. Finally, we discuss reproduction as a part of decolonisation. publishedVersion